Haitian Faculty Perceptions of Students’ Competence at Graduation: An Opportunity for Curricul a Modification - Absalon Pierre; Marie Christelle Calixte; Kelly Moore; J. C. Bunch; T. Grady Roberts (Journal of International Agricultural and Extension Education, 2018)
The contribution of agricultural universities to long-term food security in developing countries is widely acknowledged. The extent to which these universities in each country are helping students develop the requisite competence to meet employment needs is unknown. The purpose of this study was to explore Haitian faculty members’ perceptions of student competence at graduation. Semi-structured interviews were conducted with 37 lecturers who taught at five of the major agricultural universities in Haiti. The results of this revealed that (a) the employment conditions for university graduates were challenging; (b) faculty did not believe it was important for their students to graduate proficient in all the GFRAS New Extensionist competency areas; (c) faculty believed students should have research skills, the ability to be self-directed, and the ability to work in teams; and (d) faculty generally believed their institutions were producing graduates with the competencies needed for employment, although several lecturers identified specific areas for improvement. Recommendations for curricula reform and additional research are suggested
Keywords: Haiti; agriculture; extension; post-secondary education; research